Old-Age Disability and Wealth among Return Mexican Migrants from the United States - Wong, Rebeca (2010)
OBJECTIVE: To examine the old-age consequences of international migration with a focus on disability and wealth from the perspective of the origin country. METHODS: Analysis sample includes persons aged 60+ from the Mexican Health and Aging Study, a national survey of older-adults in Mexico in 2001. Univariate methods are used to present a comparative profile of return migrants. Multivariate models are estimated for physical disability and wealth. RESULTS: Gender differences are profound. Return migrant women are more likely to be disabled while men are wealthier than comparable older adults in Mexico. DISCUSSION: Compared to current older adults, younger cohorts of Mexico-U.S. migrants increasingly include women, and more migrants seem likely to remain in the United States rather than return, thus more research will be needed on the old-age conditions of migrants in both countries.